Mapping a comprehensive assessment tool to a holistic definition of health for person-centred care planning in home care: a modified eDelphi study - A. Fowokan; J.L. Giosa; M. Saari; P. Holyoke (BMC, 2023)
Abstract Background Researchers in the Netherlands proposed the Pillars for Positive Health (PPH) as a broadly encompassing health definition to support more realistic and meaningful care planning for people living with chronic disease and other life-long health conditions. The PPH was subsequently converted to the My Positive Health (MPH) spider web visualization tool. This study sought to identify opportunities for more person-centred care planning at the point of care in home care, using the MPH tool as a framework to link comprehensive assessment and dialogue-based goal-setting. Methods A modified eDelphi method was used to conduct domain mapping with a purposively sampled expert panel (n = 25). The panel consisted of researchers, health care providers, older adults and caregivers. A two-stage eDelphi process was conducted, with each stage consisting of three survey rounds. In the first stage, participants were asked to map 201 elements of the interRAI Home Care (interRAI HC) comprehensive assessment tool to the six MPH domains or "No pillar of best fit". The second stage focused on identifying opportunities to adapt or expand comprehensive assessment as it relates to the MPH domains. Results In Stage 1, 189 of 201 elements reached consensus in domain mapping. These included: 80 elements for Bodily Functions, 32 for Daily Functioning, 32 for Mental Wellbeing, 24 for Quality of Life, 10 for Participation, and 1 for Meaningfulness. Ten elements were identified to have no pillar of best fit. The 12 elements that did not reach consensus in Stage 1 formed the basis for Stage 2, where expert panel participants proposed four new assessment elements in Meaningfulness and Participation and 11 additional descriptors across the six MPH domains. Of these, two elements and nine of the 11 descriptors reached consensus. Conclusion Findings show that elements of the interRAI HC are oriented toward the physical, functional, and mental health domains. Consequently, complementary assessment elements and/or tools may be needed to support comprehensive assessment of 'Meaningfulness' and 'Participation' in person-centred home and community care. Additional descriptors may also be needed to aid communication regarding the understanding and application of MPH domains.